Dietary sodium and plasma volume levels with exercise - Luetkemeier, M. J.; Coles, M. G.; Askew, E. W. (Sports Medicine, 1997)
Sodium is the major cation of the extracellular fluid and has a potent influence on fluid movement. Sodium has been likened to a sponge that draws fluids into the extracellular space, including the plasma volume, to equalize gradients in concentration. Conventional wisdom suggests limiting dietary intake of Na+ to decrease risk of hypertension. However, there are some extreme occupational or exercise-related conditions where sweat losses are great and Na+ losses may exceed normal dietary intake. This can occur acutely such as in an ultra-endurance event or chronically as in hard manual work in the hear. In such cases, additional Na+ in the form of a higher Na+ diet or adding Na+ to beverages used for fluid replacement may be warranted. A higher Na+ diet also appears to accelerate the cardiovascular and thermoregulatory adaptations that accompany heat acclimation or short term exercise training. Saline ingestion before exercise causes an expansion of plasma volume at rest and throughout the subsequent exercise bout. This expansion of plasma volume alters cardiovascular and thermoregulatory responses to exercise in ways that may lead to beneficial changes in endurance exercise performance. Plasma volume expansion also occurs with saline infusion during exercise, but exercise performance advantages have yet to be reported. The purpose of this article is to review the literature concerning dietary sodium and its influence on fluid balance, plasma volume and thermoregulation during exercise. It contains 2 major sections. First, we will discuss manipulations in daily Na+ intake initiated before or throughout an exercise regime. Second, we will examine studies where an acute Na+ load was administered immediately before or during an exercise trial. The dependent variables that we will discuss pertain to: (i) body water compartments, i.e. plasma volume; (ii) thermoregulatory variables, i.e. core temperature and sweat rate; (iii) cardiovascular variables, i.e. heart rate and stroke volume; and (iv) performance, i.e. time trial performance and time to exhaustion. Particular attention will be given to the route by which Na+ was administered, the environmental conditions, the level of acclimation of the participants and specifics relating to Na+ administration such as the osmolality of the Na(+)-containing beverage.